2011
DOI: 10.1002/ece3.24
|View full text |Cite
|
Sign up to set email alerts
|

Do mycorrhizal network benefits to survival and growth of interior Douglas‐fir seedlings increase with soil moisture stress?

Abstract: Facilitation of tree establishment by ectomycorrhizal (EM) networks (MNs) may become increasingly important as drought stress increases with climate change in some forested regions of North America. The objective of this study was to determine (1) whether temperature, CO2 concentration ([CO2]), soil moisture, and MNs interact to affect plant establishment success, such that MNs facilitate establishment when plants are the most water stressed, and (2) whether transfer of C and water between plants through MNs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…This is a common pattern that has been described in several ecosystems and taxonomic groups worldwide (Jonsson et al, 1999;Horton and Bruns, 2001;Izzo et al, 2005;Gebhardt et al, 2007;Courty et al, 2008;Wang et al, 2012). In addition, all the EcMF registered in the seedlings were also found in the other plant categories (Table 1), as observed in Quercus liaotungensis (Wang et al, (Jonsson et al, 1999) and P. menziesii (Bingham and Simard, 2011). These findings support the fact that the EcMF colonizing naturally established seedlings are largely the same species which are present in the surrounding tree roots, which constitute a fungal inoculum source.…”
Section: Ectomycorrhizal Fungal Diversity and Community Dynamicssupporting
confidence: 74%
“…This is a common pattern that has been described in several ecosystems and taxonomic groups worldwide (Jonsson et al, 1999;Horton and Bruns, 2001;Izzo et al, 2005;Gebhardt et al, 2007;Courty et al, 2008;Wang et al, 2012). In addition, all the EcMF registered in the seedlings were also found in the other plant categories (Table 1), as observed in Quercus liaotungensis (Wang et al, (Jonsson et al, 1999) and P. menziesii (Bingham and Simard, 2011). These findings support the fact that the EcMF colonizing naturally established seedlings are largely the same species which are present in the surrounding tree roots, which constitute a fungal inoculum source.…”
Section: Ectomycorrhizal Fungal Diversity and Community Dynamicssupporting
confidence: 74%
“…The EM fungal community of cohort 2 exhibited the same pattern as cohort 1 in response to mesh treatment, at the driest sites. This apparent increase in strength of network effects under water-stressed conditions is buttressed by data we have for seedling growth and hydraulic redistribution of water (Bingham and Simard 2011).…”
Section: Effects Of Mns On Community Similaritymentioning
confidence: 69%
“…Ectomycorrhizal (EM) networks (MN) are known to facilitate seedling establishment (Dickie et al 2002(Dickie et al , 2005McGuire 2007;Teste et al 2009;Booth and Hoeksema 2010;Bingham and Simard 2011). They appear to be most beneficial when the seedling is establishing in soils that are deficient of EM propagules or soil resources (Dickie et al 2002(Dickie et al , 2005McGuire 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In water-limited ecosystems soil N is positively correlated with soil organic matter content, and soil organic matter increases water-holding capacity and infiltration rates. Thus, in water-limited ecosystems, soil fertility is likely to be negatively correlated with plant tissue d 13 C. Any alleviation of water deficiency in 35-lm mesh could have occurred through EM uptake of soil water independent of the established tree, or through translocation of water to the seedling that was hydraulically redistributed to the EM network by the tree (Querejeta and others 2003;Egerton-Warburton and others 2007;Bingham and Simard 2011a). Other studies have shown strong evidence for hydraulically redistributed water from conifer trees to seedlings through EM networks (Warren and others 2008;Booth and Hoeksema 2010).…”
Section: Em Network Enhancement Of Establishmentmentioning
confidence: 99%
“…There is also evidence that both seedlings and mycorrhizal mycelia receive hydraulically redistributed water from mature trees in a number of ecosystems, that this transfer is facilitated by EM networks, and that this facilitation is likely to occur in P. menziesii var. glauca forests (Querejeta and others 2003;others 2002, 2006;Egerton-Warburton and others 2007;Schoonmaker and others 2007;Bingham and Simard 2011a).…”
Section: Introductionmentioning
confidence: 95%